Comunidades y aprendizaje informal: Las narrativas rurales de dos cooperativistas - Rocío Belén Martín; Emiliano Foresto; Danilo Silvio Donolo (Universidade Federal do Norte do Tocantins, 2021)
In education, the possibility of narrating and using stories pursues deep objectives based on knowledge, identities, values and worldviews, which are related to what human beings are expected to be. Therefore, it is important that schools incorporate informal narratives in the teaching of different disciplines. From a multiple case study we seek to understand from the narratives the forms and meanings that denote rural contexts. Two people who are part of two cooperatives participated in the study; a permacultural artistic cooperative and a dairy farming cooperative, located in the province of Córdoba, Argentina. The narratives are described and analyzed according to three dimensions: trajectories of participation in the territory, education for and with the community, and cooperative and sovereign practices; these aspects allow us to analyze the narratives and move towards an interaction in diverse ecologies and contexts. Among the main results, it is observed that the trajectories of labor participation within each cooperative respond as a whole to diverse educational and participatory experiences that are intertwined and re-signified in multiple ways; giving meaning and allowing the development of new ways of looking, feeling and situating oneself in the world. Finally, we reflect on rural narratives as forms and meanings to point to new learning and innovative practices.